Population growth and status of california sea lions. Issue 3 (17th January 2018) - Laake, Jeffrey L.; Lowry, Mark S.; DeLong, Robert L.; Melin, Sharon R.; Carretta, James V.
ABSTRACT: The California sea lion ( Zalophus californianus ) population in the United States has increased steadily since the early 1970s. The Marine Mammal Protection Act of 1972 (MMPA) established criteria for management of marine mammals based on the concept of managing populations within the optimal sustainable population (OSP), defined as a range of abundance from the maximum net productivity level (MNPL) to carrying capacity ( K ). Recent declines in California sea lion pup production and survival suggest that the population may have stopped growing, but the status of the population relative to OSP and MNPL is unknown. We used a time series of pup counts from 1975 to 2014 and a time series of mark‐release‐resight‐recovery data from 1987 to 2015 for survival estimates to numerically reconstruct the population and evaluate the current population status relative to OSP using a generalized logistic model. We demonstrated that the population size in 2014 was above MNPL and within its OSP range. However, we also showed that population growth can be dramatically decreased by increasing sea surface temperature associated with El Niño events or similar regional ocean temperature anomalies. In this analysis we developed a critical tool for management of California sea lions that provides a better understanding of the population dynamics and a scientific foundation upon which to base management decisions related to complex resource issues involving this species. Published 2018. This article is a U.S. Government work and is in the public domain in the USA. Abstract : We used a combination of 39 years of pup counts, mark‐resight survival estimates, and mortality associated with commercial fisheries to reconstruct the California sea lion population growth and current size after more than 40 years of protection under the Marine Mammal Protection Act. We conclude that the California sea lion population has achieved maximum net productivity and optimum sustainable population levels as defined in the law; however, the population growth is sensitive to changing environmental conditions that affect survival and birth rates and we stress the importance of continued monitoring of the population as it responds to environmental and anthropogenic changes that may alter its status.